Anti-Inflammatory Activity of Glabralactone, a Coumarin Compound from Angelica sinensis, via Suppression of TRIF-Dependent IRF-3 Signaling and NF-κB Pathways - Choi, Tae Jun; Song, Jayoung; Park, Hyen Joo; Kang, Sam Sik; Lee, Sang Kook (Mediators of Inflammation, 2022)
The dried root of Angelica sinensis (A. sinensis) has been widely used in Chinese traditional medicine for various diseases such as inflammation, osteoarthritis, infections, mild anemia, fatigue, and high blood pressure. Searching for the secondary metabolites of A. sinensis has been mainly conducted. However, the bioactivity of coumarins in the plant remains unexplored. Therefore, this study was designed to evaluate the anti-inflammatory activity of glabralactone, a coumarin compound from A. sinensis, using in vitro and in vivo models, and to elucidate the underlying molecular mechanisms of action. Glabralactone effectively inhibited nitric oxide production in lipopolysaccharide- (LPS-) stimulated RAW264.7 macrophage cells. The downregulation of LPS-induced mRNA and protein expression of iNOS, TNF-α, IL-1β, and miR-155 was found by glabralactone. The activation of NF-κB and TRIF-dependent IRF-3 pathway was also effectively suppressed by glabralactone in LPS-stimulated macrophages. Glabralactone (5 and 10 mg/kg) exhibited an in vivo anti-inflammatory activity with the reduction of paw edema volume in carrageenan-induced rat model, and the expressions of iNOS and IL-1β proteins were suppressed by glabralactone in the paw soft tissues of the animal model. Taken together, glabralactone exhibited an anti-inflammatory activity in in vitro and in vivo models. These findings reveal that glabralactone might be one of the potential components for the anti-inflammatory activity of A. sinensis and may be prioritized in the development of a chemotherapeutic agent for the treatment of inflammatory diseases.